2019
DOI: 10.1007/s11606-019-05106-3
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Polypharmacy and Physical Function in Older Adults: a Systematic Review

Abstract: BACKGROUND: Reduced physical function and polypharmacy (PPha) are two highly prevalent negative effects of aging, which are expected to increase more, since demographic aging is expected to grow rapidly within the next decades. Previous research suggests that polypharmacy (PPha) is a predictor of poor physical function and vice versa in older adults and therefore we conducted a systematic review of the literature to summarize and critically analyze the relationship between physical function and PPha and vice v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 56 publications
(146 reference statements)
6
33
3
1
Order By: Relevance
“… 14 , 23 , 32 , 51 , 52 , 61 , 65 Aside from the use of PIMs, the combination of different medications can lead to drug interactions that could have exacerbated the adverse effects experienced by older adults, thereby leading to higher propensity for impaired physical function. 10 Furthermore, adverse drug reactions can occur independently of PIMs, which can contribute to accentuating the impact on physical function. 67 Anticholinergic cognitive burden is also associated with increased susceptibility of delirium, longer hospital stays and increased prescription of more medications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 14 , 23 , 32 , 51 , 52 , 61 , 65 Aside from the use of PIMs, the combination of different medications can lead to drug interactions that could have exacerbated the adverse effects experienced by older adults, thereby leading to higher propensity for impaired physical function. 10 Furthermore, adverse drug reactions can occur independently of PIMs, which can contribute to accentuating the impact on physical function. 67 Anticholinergic cognitive burden is also associated with increased susceptibility of delirium, longer hospital stays and increased prescription of more medications.…”
Section: Discussionmentioning
confidence: 99%
“… 6 Inappropriate prescriptions have been shown to be associated with a significant decline in physical performance, 7 ADL during hospitalisation, 8 as well as falls and injuries in frail older adults. 9 Previous reviews have examined associations between polypharmacy and physical function in older adults, 10 and between inappropriate medication use and functional decline. 11 …”
Section: Introductionmentioning
confidence: 99%
“…Polypharmacy has been shown to be associated with a physical impairment in older adults [ 36 , 85 , 86 ]. A systematic review on the association between polypharmacy and physical function in older adults concluded that there is a strong bidirectional relationship between polypharmacy and physical function [ 87 ]. However, a causal relationship based on the 18 observational studies included in that review could not be proven [ 87 ].…”
Section: Search Strategymentioning
confidence: 99%
“…A systematic review on the association between polypharmacy and physical function in older adults concluded that there is a strong bidirectional relationship between polypharmacy and physical function [ 87 ]. However, a causal relationship based on the 18 observational studies included in that review could not be proven [ 87 ]. The authors concluded that objective measures of physical function and polypharmacy are necessary to prove this causal relationship in future studies [ 87 ].…”
Section: Search Strategymentioning
confidence: 99%
See 1 more Smart Citation